ANALISIS KESULITAN PEMECAHAN MASALAH GEOMETRI BANGUN DATAR PADA SISWA KELAS V SD MIS ALWASLIYAH - Anim, Anim; Indah, Siti Nur; Nainggolan, Hanisa Romadona; Al-hafizah, Yurinda Vilga (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to describe the types of difficulties experienced by fifth-grade students at MIS Al- Wasliyah in solving geometry problems involving plane figures. Tshis reserch employed a descroptive qualitative approach with data collected through problem-solving tests, semi-structured interviews, and observations during the completion of tasts. The research subject consisted of 17 students who had previously learned the topic of plane figures. The result indicate that students encountered difficulties in three main indicators: identifying elements of plane figures (58,8%), selecting and applying appropriate formulas for area and perimeter (70,5%), and organizing problem solving steps systematlically (82,3%). These difficulties were caused by limited conceptual understanding,students tendency to memorize formulas without connecting them to contextual problems, and their lack of habituation in following systematic problem-solving procedures. Nevertheless, some students demonstrated good understanding, as evidenced by their ability to identify essential elements, choose suitable formulas, and performs calculations correctly. The study concludes that learning activities should place greater emphasis on strengthening conceptual understanding and developing students abilities to apply complete and structured problem-solving strategies. Keywords: geometry; plane figures; problem solving; learning difficulties; elementary students Abstrak: Penelitian ini bertujuan untuk mendeskripsikan bentuk-bentuk kesulitan yang dialami siswa kelas V MIS AL-Wasliyah dalam menyelesaikan masalah geometri bangun datar. Metode penelitian yang digunakan adalah pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa tes pemecahan masalah, wawancara semi-terstruktur, dan observasi selama proses pengerjaan soal. Subjek penelitian terdiri dari 17 siswa yang telah mempelajari materi bangun datar. Hasil penelitian menunjukkan bahwa siswa mengalami kesulitan pada tiga indikator utama, yaitu mengidentifikasi unsur bangun datar (58,8%) memilih dan menggunakan rumus luas maupun keliling (70,5%) serta menyusun langkah penyelesaian secaara runtut (82,3%). Kesulitan tersebut disebabkan oleh kurangnya pemahaman konsep dasar, kecenderungan siswa menghafal rumus tanpa memahami konteks, serta ketidakterbiasaan mengikuti prosedur pemecahan masalah secara sistematis. Meskipun demikian, sebagaian siswa telah menunjukkan pemahaman yang baik melalui kemampuan mengidentifikasi unsur bangun, memilih rumus yang sesuai, dan melakukan perhitungan dengan benar. Penelitian ini menyimpulkan bahwa diperlukan pembelajaran yang lebih menekankan pemahaman konsep dan pembiasaan strategi pemecahan masalah secara lengkap. Kata Kunci: geometri; bangun datar; pemecahan masalah; kesulitan belajar; siswa sekolah dasar.